Milking routines and prevalence of mastitis in dairy farms in Tajikistan - Carlén, Sandra (SLU/Dept. of Clinical Sciences (until 231231), 2018)
Tajikistan is the poorest of the former Soviet Union countries. Agriculture is important for the livelihood of the rural population and so is the dairy industry. In recent years, investment has been made in the dairy industry and by identifying areas of improvement, the economy of the country could be improved. The purpose of this study was to observe milking routines and to investigate the prevalence of mastitis in large dairy farms in the region around the capital city.